Temperature sensor containing rGO / ln2O3 / SnMoO4 and preparation method and application thereof
By using the combination of rGO/ln2O3/SnMoO4 nanomaterials and ethyl cellulose flexible films, the existing flexible temperature sensors have been solved, and a flexible temperature sensor with high sensitivity and wide detection range is realized, with good flexibility and economic benefits.
Patent Information
- Application Number
- CN202510046850.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-15
AI Technical Summary
Existing flexible temperature sensors have problems such as poor stability, low sensitivity, narrow detection range and complex preparation process, which are difficult to meet the needs of high sensitivity and wide detection range.
The rGO/ln2O3/SnMoO4 nanomaterial was used as the temperature-sensitive material, and the nanomaterial was spin-coated on the ethyl cellulose flexible film to prepare a flexible temperature sensor with a high sensitivity and wide detection range.
It realizes high temperature sensitivity coefficient and wide detection range (25~105℃), and has good flexibility and stability, and is simple in preparation and low cost.
Smart Images

Figure CN119822400A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of temperature sensors, in particular to a temperature sensor containing rGO / ln2O3 / SnMoO4, a preparation method thereof and applications thereof. Background Art
[0002] Temperature, as one of the most common physical quantities, can characterize the degree of hotness or coldness of an object. In the fields of medical treatment, industry, agriculture, etc., there is a general demand for measuring temperature parameters. Traditional high-sensitivity temperature sensors generally use metal or semiconductor materials as the main temperature-sensitive components, and have stable performance and are widely used. However, the temperature sensors made of metal or semiconductor materials have poor flexibility, and there are difficulties in their application in the field of flexible temperature sensing. At present, flexible temperature sensors are widely used in electronic skin, medical monitoring, industrial production, etc. because of their good deformation capabilities such as bendability, stretchability, and foldability. Usually, flexible temperature sensors are mainly formed by directly forming a film with flexible temperature-sensitive materials, or a flexible film substrate is combined with a metal or semiconductor temperature-sensitive material. However, the flexible temperature sensors currently developed generally have problems such as poor stability of the temperature sensor, low sensitivity, narrow detection range, and complex preparation process. In view of this, the present invention has developed a flexible temperature sensor with high sensitivity and a wide temperature detection range. Summary of the invention
[0003] In order to solve the above problems, the purpose of the present invention is to provide a temperature sensor containing rGO / ln2O3 / SnMoO4, a preparation method thereof and an application thereof. The temperature sensor of the present invention has the advantages of high temperature sensitivity coefficient, wide temperature detection range, good flexibility, etc., and the preparation process is simple, and the temperature-sensitive material is in close contact with the flexible material.
[0004] To achieve the above objectives, the technical solution of the present invention is as follows:
[0005] A method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 comprises the following steps:
[0006] S1. Dispersing rGO and trivalent indium salt in an alcohol organic solution, then dropping an ammonia solution, and heating in a water bath at 60 to 120° C. for 1 to 4 hours, then filtering, washing, drying, and calcining the solid for 3 to 6 hours to obtain rGO / ln2O3; wherein 0.02 to 0.04 moles of trivalent indium salt are added per gram of rGO;
[0007] S2, dispersing rGO / ln2O3 and divalent tin salt in deionized water, passing inert gas into the above solution to exclude air, stirring for 1 to 3 hours under the protection of inert gas to make the solution evenly dispersed, then dropping molybdate solution, and reacting at 50 to 90°C for 2 to 5 hours, washing and drying the filtered solid to obtain rGO / ln2O3 / SnMoO4 nanomaterials; wherein 0.001 to 0.004 mole of divalent tin salt is added for each gram of rGO / ln2O3;
[0008] S3. A flexible film is prepared by using ethyl cellulose, and then the rGO / ln2O3 / SnMoO4 nanomaterial is dissolved in anhydrous ethanol to form a temperature-sensitive material solution, and the temperature-sensitive material solution is spin-coated on the film to obtain a flexible temperature sensor; the thickness of the flexible film is 0.1 to 0.5 mm, and 0.05 to 0.5 grGO / ln2O3 / SnMoO4 nanomaterial is applied per square centimeter of the flexible film.
[0009] As a specific embodiment of the present invention, in step S1, the indium salt is indium trichloride, indium nitrate, a hydrate of indium trichloride or a hydrate of indium nitrate, and the calcination temperature ranges from 300 to 500°C.
[0010] The alcohol organic solution in the present invention can be selected from methanol, ethanol and the like.
[0011] As a specific embodiment of the present invention, in step S2, the tin salt is stannous chloride, stannous sulfate or a hydrate of stannous chloride.
[0012] In the present invention, the inert gas may be N2, Ar, He, or the like.
[0013] As a specific embodiment of the present invention, the preparation of a flexible film using ethyl cellulose comprises the following steps: dissolving ethyl cellulose in an organic solvent, placing the ethyl cellulose in a smooth mold and evaporating the solvent in an environment of 40°C.
[0014] Furthermore, the organic solvent is one or more of tetrahydrofuran, N,N-dimethylformamide or ethanol.
[0015] As a specific embodiment of the present invention, in step S3, the mass ratio of rGO / ln2O3 / SnMoO4 to anhydrous ethanol is 1:(20-100).
[0016] A temperature sensor containing rGO / ln2O3 / SnMoO4 is prepared by the above method.
[0017] A temperature sensor containing rGO / ln2O3 / SnMoO4 is used to detect the temperature of 25°C to 105°C.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention is a flexible sensor using ternary rGO / ln2O3 / SnMoO4 nanomaterials as temperature-sensitive materials, which has a high temperature sensitivity coefficient within a wide temperature detection range (25-105°C) and has good stability and mechanical flexibility.
[0020] Compared with the general method, the flexible temperature sensor containing ternary rGO / ln2O3 / SnMoO4 prepared by the present invention has simple equipment and preparation process, low cost and good economic benefit. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a scanning electron microscope image of the temperature sensor prepared in Example 1;
[0022] Figure 2 The resistance change rate-temperature response curve of the temperature sensor prepared in Example 1;
[0023] Figure 3 This is a test diagram of the response time and recovery time of the temperature sensor prepared in Example 1;
[0024] Figure 4 This is a stability diagram of the temperature sensor prepared in Example 1 under different temperature environments;
[0025] Figure 5 This is a test diagram of the temperature sensor prepared in Example 1 during a cycle test at 25°C to 45°C;
[0026] Figure 6 This is the tensile stress-strain curve of the temperature sensor prepared in Example 1. DETAILED DESCRIPTION
[0027] The specific implementation methods of the present invention will be described clearly and completely below with reference to examples. Obviously, the examples described are only some embodiments of the present invention, not all embodiments. The experimental methods used in the following examples are conventional methods unless otherwise specified; the materials, reagents, etc. used therein, unless otherwise specified, can all be obtained from commercial channels.
[0028] In the following examples, ethyl cellulose (CAS No.: 9004-57-3) was purchased from Merck, Germany.
[0029] Example 1
[0030] S1. Disperse 0.1 g rGO and 0.8 g InCl3·4H2O in 100 ml ethanol solution, then drop 10 mL ammonia solution (25 wt%) into the above solution, and heat in a water bath at 80 ° C for 3 h. After filtering, washing and drying, the solid was placed in a muffle furnace and calcined at 350 ° C for 4 h to obtain rGO / ln2O3.
[0031] S2. Disperse 0.2 g rGO / ln2O3 and 0.1 g SnCl2·2H2O in 50 mL deionized water, stir under Ar protection for 1 h, then drop 0.2 g / L K2MoO4 solution (50 mL) into the above solution, and react at 70 °C for 3 h. After cooling, filter to obtain the solid, wash and dry it, and then dry it at 60 °C for 6 h to obtain rGO / ln2O3 / SnMoO4 nanomaterials.
[0032] S3. Dissolve 2 g of ethyl cellulose in 100 mL of N,N-dimethylformamide, place it in a smooth mold and evaporate the solvent in a 40 °C environment to prepare a flexible film with a thickness of 0.2 mm, then cut it into a square film of 1×1 cm, and then disperse 0.1 g of rGO / ln2O3 / SnMoO4 in 5 mL of anhydrous ethanol and spin-coat it on the square film to obtain a flexible temperature sensor.
[0033] Example 2
[0034] S1. Disperse 0.1 g rGO and 0.8 g InCl3·4H2O in 100 ml ethanol solution, then drop 10 mL ammonia solution (25 wt%) into the above solution, and heat in a water bath at 60 ° C for 3 h. After filtering, washing and drying, the solid was placed in a muffle furnace and calcined at 300 ° C for 4 h to obtain rGO / ln2O3.
[0035] S2. Disperse 0.2 g rGO / ln2O3 and 0.05 g SnCl2·2H2O in 50 mL deionized water, stir under Ar protection for 1 h, then drop 0.2 g / L K2MoO4 solution (50 mL) into the above solution, and react at 50 °C for 3 h. After cooling, filter to obtain the solid, wash and dry it, and then dry the solid at 60 °C for 6 h to obtain rGO / ln2O3 / SnMoO4 nanomaterials.
[0036] S3. Dissolve 2 g of ethyl cellulose in 100 mL of N,N-dimethylformamide, place it in a smooth mold and evaporate the solvent in a 40 °C environment to prepare a flexible film with a thickness of 0.2 mm, then cut it into 1×1 cm square films, and then disperse 0.1 g of rGO / ln2O3 / SnMoO4 in 5 mL of anhydrous ethanol and spin-coat it on the square film to obtain a flexible temperature sensor.
[0037] Example 3
[0038] S1. Disperse 0.1 g rGO and 0.8 g InCl3·4H2O in 100 ml ethanol solution, then drop 10 mL ammonia solution (25 wt%) into the above solution, and heat in a water bath at 120 ° C for 3 h. After filtering, washing and drying, the solid was placed in a muffle furnace and calcined at 450 ° C for 4 h to obtain rGO / ln2O3.
[0039] S2. Disperse 0.2 g rGO / ln2O3 and 0.15 g SnCl2·2H2O in 50 mL deionized water, stir under Ar protection for 1 h, then drop 0.2 g / L K2MoO4 solution (50 mL) into the above solution, and react at 70 °C for 3 h. After cooling, filter to obtain the solid, wash and dry it, and then dry the solid at 90 °C for 6 h to obtain rGO / ln2O3 / SnMoO4 nanomaterials.
[0040] S3. Dissolve 2 g of ethyl cellulose in 100 mL of N,N-dimethylformamide, place it in a smooth mold and evaporate the solvent in a 40 °C environment to prepare a flexible film with a thickness of about 0.2 mm, then cut it into 1×1 cm square films, and then disperse 0.1 g of rGO / ln2O3 / SnMoO4 in 5 mL of anhydrous ethanol and spin-coat it on the square film to obtain a flexible temperature sensor.
[0041] Comparative Example 1
[0042] S1. Disperse 0.1 g rGO and 0.8 g InCl3·4H2O in 100 ml ethanol solution, then drop 10 mL ammonia solution (25 wt%) into the above solution, and heat in a water bath at 80 ° C for 3 h. After filtering, washing and drying, the solid was placed in a muffle furnace and calcined at 350 ° C for 4 h to obtain rGO / ln2O3.
[0043] S2. Dissolve 2 g of ethyl cellulose in 100 mL of N,N-dimethylformamide, place it in a smooth mold and evaporate the solvent in a 40 °C environment to prepare a flexible film with a thickness of about 0.2 mm, then cut it into 1×1 cm square films, and then disperse 0.1 g of rGO / ln2O3 in 5 mL of anhydrous ethanol and spin-coat it on the square film to obtain a flexible temperature sensor.
[0044] Comparative Example 2
[0045] S1. Disperse 0.1 g rGO and 0.2 g SnCl2·2H2O in 100 mL ethanol solution, stir under Ar protection for 1 h, then drop 0.2 g / L K2MoO4 solution (100 mL) into the above solution, and react at 70 °C for 3 h. After cooling, filter to obtain the solid, wash and dry it, and then dry it at 60 °C for 6 h to obtain rGO / SnMoO4 nanomaterials.
[0046] S3. Dissolve 2 g of ethyl cellulose in 100 mL of N,N-dimethylformamide, place it in a smooth mold and evaporate the solvent in a 40 °C environment to prepare a flexible film with a thickness of about 0.2 mm, then cut it into 1×1 cm square films, and then disperse 0.1 g of rGO / SnMoO4 in 5 mL of anhydrous ethanol and spin coat it on the square film to obtain a flexible temperature sensor.
[0047] Comparative Example 3
[0048] S1. Disperse 0.8 g InCl3·4H2O in 100 ml ethanol solution, then drop 10 mL ammonia solution (25 wt%) into the above solution, and heat in a water bath at 80°C for 3 h. After filtering, washing and drying, the solid matter is placed in a muffle furnace and calcined at 350°C for 4 h to obtain In2O3.
[0049] S2. Disperse 0.08g ln2O3 and 0.1g SnCl2·2H2O in 50mL deionized water, stir under Ar protection for 1h, then drop 0.2g / L K2MoO4 solution (50mL) into the above solution, and react at 70℃ for 3h. After cooling, filter to obtain the solid, wash and dry it, and then dry it at 60℃ for 6h to obtain ln2O3 / SnMoO4 nanomaterial.
[0050] S3. Dissolve 2 g of ethyl cellulose in 100 mL of N,N-dimethylformamide, place it in a smooth mold and evaporate the solvent in a 40 °C environment to prepare a flexible film with a thickness of about 0.2 mm, then cut it into 1×1 cm square films, and then disperse 0.1 g of rGO / ln2O3 / SnMoO4 in 5 mL of anhydrous ethanol and spin-coat it on the square film to obtain a flexible temperature sensor.
[0051] Test Example 1
[0052] The flexible temperature sensing material prepared in Example 1 of the present invention was analyzed by electron scanning electron microscopy. The results are as follows: Figure 1 Observation Figure 1 The nanoparticles on the surface of the flexible temperature sensor prepared in Example 1 of the present invention are evenly dispersed, which is beneficial to the stability of the performance.
[0053] Test Example 2
[0054] The steady-state resistance of the flexible temperature sensors of Examples 1 to 3 and Comparative Examples 1 to 3 at different temperatures was measured. Specifically, the resistance of each sensor was tested at intervals of 5°C in the temperature range of 25°C to 105°C, the resistance change rate ((R-R0) / R0) at each temperature was calculated, and a resistance change rate-temperature response curve of the temperature sensor was plotted. The linear change portion of the curve was taken and the temperature coefficient of resistance (TCR) of the temperature sensor in the temperature range was calculated. The test results are shown in Tables 1 and Figure 2 .
[0055] TCR = [(R-R0) / R0]×100% / (T-T0), T is the upper limit temperature of the linear range, T0 is the lower limit temperature of the linear range, R0 is the resistance corresponding to the temperature T0, and R is the resistance corresponding to the temperature T.
[0056] Table 1 Temperature sensitivity coefficients of various temperature sensors
[0057]
[0058] As can be seen from Table 1, all embodiments and comparative examples are temperature sensors with negative temperature coefficients. From the perspective of the linear range of the detected temperature, embodiments 1 to 3 are all within the range of 25 to 105°C, which is significantly higher than comparative examples 1 to 3. At the same time, within the linear range, the temperature sensitivity coefficients of embodiments 1 to 3 are 1.13%°C. -1 ~1.29%℃ -1 , which is significantly better than 0.55%℃ of Comparative Examples 1 to 3 -1 ~0.87%℃ -1 Therefore, the use of ternary rGO / ln2O3 / SnMoO4 temperature-sensitive materials helps to improve the temperature sensitivity coefficient and detection range of the temperature sensor.
[0059] Test Example 3
[0060] The response time and recovery time of the sensors prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested. The test process was as follows: after the sensor was placed in an environment of 25°C until the resistance value stabilized, the sensor was quickly transferred to an environment of 45°C, and the time required for the sensor resistance to stabilize in the 45°C environment was tested. Then, the sensor whose resistance value was stabilized in the 45°C environment was quickly transferred to an environment of 25°C, and the time required for the sensor resistance value to stabilize was tested. The test results are shown in FIG. Figure 3 And as shown in Table 2.
[0061] It can be seen from Table 2 that after the temperature is increased from 25°C to 45°C, the response time of Examples 1 to 3 is between 25s and 29s, and the response time of Comparative Examples 1 to 3 is between 30s and 32s; after recovering from 45°C to 25°C, the recovery time of Examples 1 to 3 is between 45s and 49s, and the recovery time of Comparative Examples 1 to 3 is between 49s and 58s; Overall, the corresponding time and recovery time of the embodiments reach or exceed the optimal values of the comparative examples, and have good corresponding recovery performance, especially Example 1, whose response time is 25s and recovery time is 45s, which is significantly better than other embodiments and comparative examples.
[0062] Table 2 Response time and recovery time table of each temperature sensor at 25℃~45℃
[0063]
[0064] Test Example 4
[0065] The temperature sensor prepared in Example 1 was subjected to a cycle test experiment. One cycle test was 25°C → 60°C → 25°C. The resistance value of the sensor was measured and its resistance change rate was calculated. The results are as follows: Figure 4 As shown, after the temperature sensor has been cycled from 25°C to 60°C and then back to 25°C for 8 times, the resistance of the sensor changes very little, which indicates that the temperature sensor prepared by the present invention has good reuse performance.
[0066] Test Example 5
[0067] The stability of the temperature sensor prepared in Example 1 at different temperatures (25°C, 45°C, 60°C, 75°C, 90°C, 105°C) was tested. The results are as follows: Figure 5 As shown, the resistance of the temperature sensor changes very little within 100 minutes, indicating that the invented temperature sensor has long-term stability.
[0068] Test Example 6
[0069] The tensile stress-strain test of the temperature sensor prepared in Example 1 shows the following results: Figure 6 The results show that the flexible temperature sensor prepared by the present invention has good mechanical flexibility.
[0070] The present invention has been disclosed in the above preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be construed as limiting the scope of the present invention. Further improvements can be made without departing from the principles of the present invention, and these improvements should also be included in the scope of protection of the present invention.
Claims
1. A method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4, characterized in that: The steps include: S1. Dispersing rGO and trivalent indium salt in an alcohol organic solution, then dropping an ammonia solution, and heating in a water bath at 60 to 120° C. for 1 to 4 hours, then filtering, washing, drying, and calcining the solid for 3 to 6 hours to obtain rGO / ln2O3; wherein 0.02 to 0.04 moles of trivalent indium salt are added per gram of rGO; S2, dispersing rGO / ln2O3 and divalent tin salt in deionized water, passing inert gas to exclude air, stirring for 1 to 3 hours under the protection of inert gas to make the solution evenly dispersed, then dropping molybdate solution, and reacting at 50 to 90°C for 2 to 5 hours, washing and drying the filtered solid to obtain rGO / ln2O3 / SnMoO4 nanomaterials; wherein, 0.01 to 0.04 mole of divalent tin salt is added for each gram of rGO / ln2O3; S3. A flexible film is prepared by using ethyl cellulose, and then the rGO / ln2O3 / SnMoO4 nanomaterial is dissolved in anhydrous ethanol to form a temperature-sensitive material solution, and the temperature-sensitive material solution is spin-coated on the film to obtain a flexible temperature sensor; the thickness of the flexible film is 0.1 to 0.5 mm, and each square of the flexible film is coated with 0.05 to 0.5 grGO / ln2O3 / SnMoO4 nanomaterial.
2. The method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 according to claim 1, characterized in that: The indium salt is indium trichloride, indium nitrate, a hydrate of indium trichloride or a hydrate of indium nitrate, and the calcination temperature ranges from 300 to 500°C.
3. The method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 according to claim 2, characterized in that: The calcination temperature is 350°C.
4. The method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 according to claim 1, characterized in that: In step S2, the tin salt is stannous chloride, stannous sulfate or a hydrate of stannous chloride.
5. The method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 according to claim 1, characterized in that: The method for preparing a flexible film using ethyl cellulose comprises the following steps: dissolving ethyl cellulose in an organic solvent, placing the ethyl cellulose in a smooth mold and evaporating the solvent in an environment of 40° C.
6. The method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 according to claim 5, characterized in that: The organic solvent is one or more of tetrahydrofuran, N,N-dimethylformamide or ethanol.
7. The method for preparing a temperature sensor containing rGO / ln2O3 / SnMoO4 according to claim 1, characterized in that: In step S3, the mass ratio of rGO / ln2O3 / SnMoO4 to anhydrous ethanol is 1:20-100.
8. A temperature sensor containing rGO / ln2O3 / SnMoO4, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
9. An application of a temperature sensor containing rGO / ln2O3 / SnMoO4, characterized in that: Used to detect temperatures from 25°C to 105°C.